State of the art: refinement of multiple sequence alignments - Chakrabarti, Saikat (BioMed Central, 2010)
Correction to Chakrabarti S, Lanczycki CJ, Panchenko AR, Przytycka TM, Thiessen PA and Bryant SH: State of the art: refinement of multiple sequence alignments. BMC Bioinformatics 2006, 7:499.